Is irritable bowel syndrome an organic disorder? - El-Salhy, Magdy (Baishideng Publishing Group Co., Limited, 2014)
Irritable bowel syndrome (IBS) is a common gastrointestinal disorder that is generally considered to be functional because there appears to be no associated anatomical defect. Stress and psychological factors are thought to play an important role in IBS. The gut neuroendocrine system (NES), which regulates all functions of the gastrointestinal tract, consists of endocrine cells that are scattered among the epithelial cells of the mucosa, and the enteric nervous system. Although it is capable of operating independently from the central nervous system (CNS), the gut NES is connected to and modulated by the CNS. This review presents evidence for the presence of an anatomical defect in IBS patients, namely in the gastrointestinal endocrine cells. These cells have specialized microvilli that project into the lumen and function as sensors for the luminal content and respond to luminal stimuli by releasing hormones into the lamina propria, which starts a chain reaction that progresses throughout the entire NES. The changes in the gastrointestinal endocrine cells observed in IBS patients are highly consistent with the other abnormalities reported in IBS patients, such as visceral hypersensitivity, dysmotility, and abnormal secretion.